Efecto de nuevas formulaciones cúpricas sobre el crecimiento in vitro de Xanthomonas axonopodis pv citri - Mitidieri, Mariel Silvina; Brambilla, Maria Virginia; Muñoz, Soledad; Piris, Estela Beatriz; Peralta, Romina; Sánchez, Florencia; Gazzo, Gabriela (Universidad Nacional del Noroeste de la Provincia de Buenos Aires -UNNOBA, 2022)
Poster